Assessing the role of modified disbursement system in public expenditure management - Jagna-an, Peachie P.; Sarroza, Ma. Felomina B. (2006)
The purpose of this study is to assess the Modified Disbursement system of the National Government as implemented by the Bureau of the Treasury (BTr) in Public Expendixture management with the following key indicators: Safeguarding of Government funds, Funding, Payment, Encashment and Replenishment. This study specifically aims to answer the following problems: 1. What are the current practices observed by the government through the Bureau of the Treasury (BTr) on its Disbursements and Internal Control of funds?; 2. How effective is the MDS with respect to, safeguarding of government funds, funding, payment, encashment and, replenishment as implemented by the BTr; 3. How do the groups of respondents (Government Servicing Banks and BTr) view the effectiveness of MDS based on the variables mentioned; 4. What are the usual problems encountered by the respondents in the implementation of the MDS and what are the perceived solutions of the respondents to remedy the problems identified. MDS as implemented by the BTr is considered to be effective although problems might have been encountered in the process. Overall, the MDS has further strengthened the role of the BTr as the custodian of government funds. Some problems have been noted by the respondents especially in the process of replenishment, but these can be resolved through the implementation of perceived solutions of the respondents, such as operating online and full-scale computerization of the entire process since time element and work volume are the major concerns of the respondents under these two issues. The fact that replenishment is done on a daily basis makes it very procedural and routine in nature, thus the resulting solution perceived by the respondents is to do away with manual operation and adopt a system which could improve on the replenishment process. This will likewise lessen paperwork, making deadlines a lot easier to meet. The respondents agreed that a full-scale computerization of transactions between the GSBs and the BTr wold further strengthen the power of MDS as a tool to safeguard government funds. A developed electronic and online system will not just expedite the entire process but enhance control mechanisms as well. All these should start with sufficient logistics support for both the GSB and the BTr.
Research Paper (Mgt 299 - Research Methods in Management). -- [Iloilo City : UPV-CM], February 25, 2006.